Implementation of the Non-Cash Payment System Policy A Civil Servant in The Pandemic Era at Manado State University - Sekeh, Richard Haryson; Pangkey, Itje; Kairupan, Sisca Beatrix (Technium Social Sciences Journal, 2022)
A cash transaction system for paying the salaries of lecturers and employees can also cause several problems. In distributing money, the treasurer still must spend money in the bank and disburse funds to lecturers and employees. Withdrawing such large amounts of funds can pose a risk of robbery or theft on the way to the office. The length of the distribution process will cause a buildup of money in the safe that has not been channeled to the recipient. The destination study is to describe how the implementation of the non-Cash transaction system for payment of salaries of lecturers and employees at the Manado State University. This article also explains the obstacles faced in implementing the non-Cash transaction system for the number of honorariums for Lecturers and Employees at Manado State University. The research method used in this research is a qualitative research method with a descriptive approach. Qualitative research in this study collects data and information about phenomena and conditions closely related to the problem to be studied. The data collection process is obtained through interviews, documentation, and observations. The data analysis technique in this research is using data triangulation. The analysis consists of three activities: data reduction, data presentation, and drawing conclusions or verification. Discussion results show that the implementation of non-cash transactions for payment of honoraria at Manado State University still needs to be carefully prepared again. Implementing non-cash transactions for payment of honorarium for lecturers and employees at Manado State University, there is a mechanism in its implementation.